1999
DOI: 10.1080/003655999750015826
|View full text |Cite
|
Sign up to set email alerts
|

Voiding and Sexual Dysfunctions after Pelvic Fracture Urethral Injuries Treated with either Initial Cystostomy and Delayed Urethroplasty or Immediate Primary Urethral Realignment

Abstract: Sexual and voiding dysfunction after pelvic fracture posterior urethral injury seem to be the result of the injury itself, not of the immediate treatment modalities. In urethral disruption injuries, primary urethral realignment seems more favourable than suprapubic cystostomy and delayed repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 18 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…The goal of management is to realign the urethra whilst minimising the risks of ED, incontinence and subsequent urethral stricture [4] ; Table 1 [13–41] and Fig. 1 summarise the findings of the above complications in early endoscopic realignment (EER), early open primary realignment, and STDU in studies from 1990 to the present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of management is to realign the urethra whilst minimising the risks of ED, incontinence and subsequent urethral stricture [4] ; Table 1 [13–41] and Fig. 1 summarise the findings of the above complications in early endoscopic realignment (EER), early open primary realignment, and STDU in studies from 1990 to the present.…”
Section: Introductionmentioning
confidence: 99%
“…Once the PFUI is diagnosed most authors still attempt a single, gentle catheter placement at the bedside or in the operating room, by a urologist [24,38,39] . If this fails, then there are various endoscopic techniques available.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies also suggested that ED and incontinence were higher in men undergoing PR. More recent studies suggest these complications are likely related to the underlying traumatic injury, rather than the choice of immediate urethral injury management ( 27 ) however, this has yet to be established in any longitudinal comparison study as proposed here.…”
Section: Discussionmentioning
confidence: 86%
“…Asci et al published a retrospective cohort study in 1999 with 38 male patients managed with either SPT (n=18) or PR (n=20) with the primary aim of determining voiding and sexual dysfunction and evaluation of urethral stricture reformation ( 22 ). Urethral stricture rate was found to be statistically significant (83.3% SPT vs. 45.0% PR; P=0.014).…”
Section: Primary Realignment (Pr)mentioning
confidence: 99%